Diagnostic and prognostic value of interleukin-6, pentraxin 3, and procalcitonin levels among sepsis and septic shock patients: a prospective controlled study according to the Sepsis-3 definitions - Song, Juhyun; Park, Dae Won; Moon, Sungwoo; Cho, Han-Jin; Park, Jong Hak; Seok, Hyeri; Choi, Won Seok (BMC infectious diseases, 2019)
Background This study investigated the clinical value of interleukin-6 (IL-6), pentraxin 3 (PTX3), and procalcitonin (PCT) in patients with sepsis and septic shock diagnosed according to the Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3). Methods Serum levels of IL-6, PTX3, and PCT were measured in 142 enrolled subjects (51 with sepsis, 46 with septic shock, and 45 as controls). Follow-up IL-6 and PTX3 levels were measured in patients with initial septic shock within 24 h of hospital discharge. Optimal cut-off values were determined for sepsis and septic shock, and prognostic values were evaluated. Results Serum IL-6 levels could discriminate sepsis (area under the curve [AUC], 0.83–0.94, P <  0.001; cut-off value, 52.60 pg/mL, 80.4% sensitivity, 88.9% specificity) from controls and could distinguish septic shock (AUC, 0.71–0.89; cut-off value, 348.92 pg/mL, 76.1% sensitivity, 78.4% specificity) from sepsis. Twenty-eight-day mortality was significantly higher in the group with high IL-6 (≥ 348.92 pg/mL) than in the group with low IL-6 (< 348.92 pg/mL) ( P = 0.008). IL-6 was an independent risk factor for 28-day mortality among overall patients (hazard ratio, 1.0004; 95% confidence interval, 1.0003–1.0005; p = 0.024). In septic shock patients, both the initial and follow-up PTX3 levels were consistently significantly higher in patients who died than in those who recovered (initial p = 0.004; follow-up P <  0.001). Conclusions The diagnostic and prognostic value of IL-6 was superior to those of PTX3 and PCT for sepsis and septic shock.